Pagamento por performance: uma análise da gestão dos recursos financeiros do PMAQ-AB na Paraíba - Rodrigues, André Wagner Dantas (2021)
The management process in primary care has undergone changes in recent decades. One of them was the payment-for-performance process of the Access and Quality Improvement in Primary Care Program (PMAQ-AB), which innovated the method of transferring resources to primary care, adding the quality indicator to assess the teams. The PMAQ-AB allocated financial resources to the municipality according to the performance evaluation of the teams participating in the program, regarding the quality and access of services offered to the population. However, the program did not define how these resources should be applied at the municipal level, leaving the municipalities to agree locally, through laws, decrees or ordinances created for this purpose. The PMAQ-AB had its end decreed in the year 2019. This study aims to analyze the management of resources of the PMAQ-AB and its relationship with the performance of municipalities in Paraíba participating in the program. This is a descriptive, cross-sectional, analytical research with a quantitative approach, with 219 municipal managers. The results of this work came from two databases. The data underwent an exploratory descriptive analysis and the use of the logistic regression model. The results were presented in two-article format. The first article was descriptive and portrayed how the transfer of resources occurred in the three evaluation cycles. The article showed that most municipalities in Paraíba have adopted a municipal law as a rule to regulate the use of financial incentives under the PMAQ-AB. External evaluation was the main criterion for transferring financial resources to the health teams. During the cycles, more actors received resources in addition to the minimum team of the family health strategy and the transfer was made on a biannual and annual basis, with around 40% to 50% of the amount allocated to the teams and the remainder invested in improvements to the work conditions. The second article, on the other hand, was used only with data referring to the third cycle of the program's evaluation and pointed out, through the logistic regression model, which municipalities used the criterion of the result of the external evaluation to transfer resources; they transferred resources to the support/manager beyond the minimum team of the family health strategy; adopted the monthly frequency for transfer and transferred a percentage of 0 to 20% of the value of resources to the teams, had more chances of having a better performance in the PMAQ-AB certification. It is concluded that this research allowed the identification of relevant aspects about how the PMAQ-AB resources were implemented at the local level by the municipalities of a state with high ESF coverage and broad adherence to the Program. In addition, it allowed the identification of more relevant ways to transfer resources, in order to achieve better results from primary care teams. This allows for the identification of potential vectors to be considered by the managers of the three spheres in future pay-for-performance policies, which gain greater relevance at a time when the PMAQ-AB, as a form of composition of funding for primary care, was discontinued.